(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The healthcare system must take into account the individual needs of every patient and therefore requires a personalized approach. Personalized medicine, also known as the individual approach, is based on adapting medical care to each patient’s genetic, environmental, and lifestyle factors. This article discusses the introduction of personalized medicine into the healthcare system, emphasizing its significance, advantages, and future prospects. By using genetic information, medical imaging, and other biomedical data, personalized medicine enables the creation of treatment methods that are specifically tailored to the characteristics of each patient. As a result, it ensures more effective and goal-oriented medical care. Furthermore, this approach plays an important role in the efficient distribution of healthcare resources and the prevention of diseases, contributing to the improvement of overall public health outcomes.